UPAYA PENINGKATAN MOTIVASI BELAJAR FISIKA MENGGUNAKAN MODEL PEMBELAJARAN SCRAMBLE - Agus Santoso (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The background of this research is the low learning motivation of students of SMK Negeri 1 Ngawen. This is indicated by the lack of ability to ask questions, thoroughness in doing questions, still cheating, the desire to find learning resources and so on. The purpose of this study was to determine the use of the scramble learning model to increase motivation to learn physics in students of SMK Negeri 1 Ngawen for the 2019/2020 academic year. This type of research is classroom action research. This research was conducted in two cycles. The subjects in this study were 31 students of class X TAB B of SMK Negeri 1 Ngawen in the 2019/2020 academic year, consisting of 16 female students and 15 male students. The data were collected using the observation method, the test method, the questionnaire method and the documentation method. After the data was obtained, it was analyzed using a percentage scale. The results of the study can be concluded that through the use of scramble learning models in learning physics can increase the learning motivation of students of SMK Negeri 1 Ngawen. This can be seen from the observation data of student learning motivation increased from 46.94% in the pre-cycle to 60.81% in the first cycle and increased again to 73.39% in the second cycle. The percentage of students' motivation questionnaire increased 58.06% in the pre-cycle to 72.90% in the first cycle and to 81.29% in the second cycle. This increase in learning motivation has an effect on improving learning outcomes. This is indicated by the increase in the average score of students. The mean score of students increased from 59.98 with completeness 38.71% in the pre-cycle to 77.66 with 80.69% completeness in cycle I and increased again to 85.97 with completeness of 93.97% in cycle II.